PRELIMINARY EVALUATION OF THE ANTIMICROBIAL ACTIVITY OF DITHIOCARBAMATE RESINS BASED ON GMA-EDGMA COPOLYMERS - Costa, Luciana; Castro, Helena M.A.; Franco, Raphaela S.; Santos, Roberta Trovão; Torquato, Ezaine C.C.; Marques, Mônica R.C. (Acta Scientiae et Technicae; v. 9 n. 1 (2021), 2021)
In this work we report the development of a new strategy for the preparation of dithiocarbamate resins based on glycidyl methacrylate-ethylene glycol dimethacrylate (GMA-EDGMA) copolymers. The methodology for introduction of the dithiocarbamate moieties on these copolymers was based on reaction with ethylenediamine, triethylenetetramine, tetraethylenepentamine and then reaction with carbon disulfide under alkaline medium. The antimicrobial activity of these products was evaluated employing inhibition halo tests against Escherichia coli (Gram-negative bacteria) and Staphylococcus aureus (Gram-positive bacteria). Data of N 2 adsorption indicated that GMA-EDGMA copolymer containg a mesoporous structure. Data of FT-IR indicated that reaction of copolymers with diamines occurred in a reazoable proportion however the reaction of the aminated derived with CS 2 occurred in lower proportion. Only the copolymer containing dithiocarbamate groups prepared by reaction with diethyltriamine and carbon disulfide showed halo of inhibition against E. Coli and S. Aureus bacteria.